2022
DOI: 10.1155/2022/6136265
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Pantoea agglomerans Bacteremia Using Oral Antibiotics

Abstract: A 30-year-old female with a medical history of gastrointestinal reflux and intravenous methamphetamine use was admitted to the hospital with complaints of fever and chills. Pantoae agglomerans was isolated in one out of two blood cultures. Although information was limited about the duration and efficacy of oral antibiotics to treat this type of infection, the patient recovered with oral antibiotic treatment following a short course of intravenous antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
2
2
0
2
Order By: Relevance
“…Some studies have found carbapenems effective against this infection 24,35 . A recent study found a 2‐day course of cephalosporins followed by a 12‐day therapy with quinolone compelling 33 . In our study, around 94.1% of infected patients had an excellent response to cephalosporins, further emphasizing their role in treating this infection, especially in uncomplicated cases.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Some studies have found carbapenems effective against this infection 24,35 . A recent study found a 2‐day course of cephalosporins followed by a 12‐day therapy with quinolone compelling 33 . In our study, around 94.1% of infected patients had an excellent response to cephalosporins, further emphasizing their role in treating this infection, especially in uncomplicated cases.…”
Section: Discussionsupporting
confidence: 62%
“…24,35 A recent study found a 2-day course of cephalosporins followed by a 12-day therapy with quinolone compelling. 33 In our study, around 94.1% of infected patients had an excellent response to cephalosporins, further emphasizing their role in treating this infection, especially in uncomplicated cases. In contrast, in cases of ongoing sepsis, we suggest catheter removal in combination with carbapenem therapy as the most effective treatment option, as seen from our data.…”
Section: Essential Aspects Percentage (Frequency)supporting
confidence: 55%
See 1 more Smart Citation
“…In pediatric patients, Pantoea species were deemed to be involved in wound infection following penetrating trauma and catheter-related bacteremia [11], postsurgical meningitis [12], bloodstream infection, sepsis or fatal infections in newborns [12][13][14][15][16][17], and nosocomial outbreaks [18][19][20][21]. In adults, wound infections [22][23][24], septic arthritis [25][26][27][28][29][30][31], prosthetic joint infections [32], osteomyelitis [33], bloodstream infections or sepsis [34][35][36][37][38][39][40][41], peritonitis in patients on peritoneal [42][43][44][45][46][47][48] or hemodialysis [49], eye infections [50][51][52][53], endocarditis [54], infection in a near-term female [55], pneumonia post-lung transplant…”
Section: Introductionmentioning
confidence: 99%
“…Dicha paciente tenía antecedentes médicos de reflujo gastrointestinal y uso de metanfetamina y heroína por vía intravenosa; ambos factores asociados a bacteriemia por P. agglomerans, este último factor se asocia con la "fiebre del algodón", una respuesta febril benigna a la producción de endotoxinas por P. agglomerans después de la introducción del algodón en el torrente sanguíneo. (12) Otro caso de infección por P. agglomerans fue reportado en un niño de 4 años inmunocompetente y sin comorbilidades, que consultó por fiebre y marcadores inflamatorios elevados. El urocultivo fue estéril.…”
Section: Introductionunclassified